New and known species of the family Leuconidae(Cumacea, Peracarida) from Antarctic deep-sea basins - Mühlenhardt-Siegel, Ute (Zootaxa, 2011)
The leuconid cumaceans of the Antarctic deep-sea basins are listed. Ten new leuconid species are described: eight species in the genus Leucon: L. (Crymoleucon) parantarcticus, L. (C.) weddellensis, L. (C.) longirhinus, L. (C.) grandidentatus, L. (Leucon) quattuormulierum, L. (L.) andeep, L. (Macrauloleucon) weigmanni and L. (M.) complexus. One new species is described for the genus Eudorella: E. flokkeri. The genus Bytholeucon was discovered for the first time in Antarctic waters with a new species, B. hartmannorum.